Online úskalia folkloristického výskumu - Eva Šipöczová (AntropoWebzin)
The problematic aspects of internet research are slowly becoming manifest in all the Humanities. The primary concern of ethnology and folkloristics is contemporary folklore – anecdotes, urban legends, rumours, conspiracy theories, all of which are abundant on the internet. Neverteless, the nature of virtual reality has given rise to new methodological problems and uncertainties. How should we collect folklore material on the internet? A conflict rages between classic face-to-face research, and the physically distanced research of the vitrual space. Virtual space has diffrent rules and principles of communication; it functions in a diffrent way. Who is our informer? who is the proprietor of folklore on the internet? And how can we give relevant context to collected materials? The next ambuscade is the fact that the internet creates a inexhaustible quantity of folklore material which lives in databases, discussion forums, emails, chatrooms, social networks, etc.--How can we use this huge database? This contribution does not profess to provide a correct methodology for conducting qualitative folklore research on the internet. Its purpose is to point out the problems and thus join the discussion already taking place around the world, and increasingly in our region.